"A study on the relationship between perception and adoption of digital banking services with reference to working women of selected districts of Saurashtra Region” - Pof. Janhavi Shah, Prof. (Dr.) Jay Talati, 3Prof. Priyal Kanabar (South Eastern European Journal of Public Health, 2025)
This research explores how working women in the Saurashtra region of Gujarat, India, perceive and adopt digital banking services, focusing on key factors like usefulness, ease of use, trust, and perceived risk. The study gathered responses from 250 participants through structured questionnaire, employing non-probability convenience sampling. Data analysis involved factor analysis, correlation, and ANOVA techniques to uncover trends and insights. Results highlight that, while digital banking is widely regarded as convenient and efficient, challenges such as securityconcerns, lack of personal interaction, and technical barriers prevent its full acceptance. Factor analysis revealed two major themes: positive perceptions, such as convenience and security, which encourage adoption, and negative aspects, like concerns over fraud and discomfort, which act as deterrents. Differences in how benefits are perceived emerged across demographic groups, but concerns were consistently noted across the board. The findings provide practical recommendations for banks and policymakers to address these challenges, improve user trust, and enhance digital banking access for working women, ultimately promoting financial inclusion in the region.